A numerical study of single air bubble formation comparison between in viscous liquid and in water. Issue 6 (4th September 2019) - Islam, Md. Tariqul; Ganesan, Poo Balan; Billah, Md. Masum; Uddin, Md. Nasir
Abstract: The performance of bubble column reactors is dependent on bubble size that is formed through a sparger. Here, a single air bubble formation (BF) using an orifice in the viscous liquid is modeled by using the volume of fluid method. The interface between the air and the liquid phase is calculated by using the continuum surface force equation. Detailed characteristics of BF such as the instantaneous contact angle, bubble departure volume, bond number due to orifice size and surface tension, and capillary number are examined for different orifice sizes at constant air flow rate boundary condition. The numerical results are validated with available correlation and experimental data for orifice bond number reported in the literature. A comparison of BF characteristics between in the viscous liquid and in the water is examined. The instantaneous contact angle decreases steeply for the orifice with small size than a large orifice. The bubble volume increases with increasing contact angle and decreasing the orifice bond number. In comparison with water, a decreasing detachment time and dome width of bubble and an increasing bubble neck elongation are found in viscous liquid and decrease with increasing bond number. Moreover, there is a minimum capillary number, where the bubble neck elongation height and breakup processes are relatively fast. This study can helpful in designing a coarse gas sparger to develop pseudo‐homogeneous bubbly flow regime at lower superficial gas velocity conditions.